Effects of a sport-specific upper-body resistance-band training program on overhead throwing velocity and glenohumeral joint range of motion - Oranchuk, D. J.; Ecsedy, E. N.; Robinson, T. L. (The Journal of Strength and Conditioning Research, 2021)
Practitioners seek optimal, yet practical means to enhance performance while aiming to minimize injury risk. Resistance bands offer portability and safety and enable similar movements to competition. However, the effect of movement-specific resistance-band training on throwing performance and markers of injury risk has yet to be elucidated. Therefore, the purpose of this study was to compare the effects of a resistance training program using resistance bands with sport-specific (SS), or general-training (GT) exercises. Twenty-eight collegiate female softball players were randomly allocated to an SS (n = 15) or GT (n = 13) 8-week resistance-band program. Dependent variables included peak and mean throwing velocity, 1 repetition maximum (1RM) cable Chop-test, and glenohumeral internal and external rotation range of motion (ROM). No significant (p = 0.338) differences were found between groups at baseline. Improvements in peak (p = 0.006, 4.9%, effect size [ES] = 0.61) and mean (p = 0.004, 3.1%, ES = 0.49) throwing velocity were seen after SS training, while the 1RM Chop-test increased in both SS (p < 0.001, 23.5%, ES = 1.06) and GT (p = 0.049, 26.1%, ES = 0.57) groups. However, no between-group differences (p = 0.109, ES = 0.17) were present in any variable. Neither the Chop-test nor shoulder internal or external ROM had more than moderate correlations with throwing velocity (r = 0.30, p = 0.119). Therefore, practitioners should not depend solely on SS resistance-band training when aiming to improve throwing velocity or measures of shoulder rotational health. However, resistance bands appear to be a practical alternative when traditional means of resistance training are not available. In addition, strength and conditioning coaches should not use the Chop-test or shoulder ROM to predict throwing performance.